2011
DOI: 10.1111/j.1747-0803.2011.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Testing Identifies Patients at Increased Risk for Morbidity and Mortality Following Fontan Surgery

Abstract: In adults with Fontan surgery, exercise test data can identify patients at increased risk of midterm morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 36 publications
2
74
2
Order By: Relevance
“…Exercise performance after palliation of complex congenital heart lesions such as the atrial switch procedure or the Fontan procedure is impaired, with a maximal oxygen consumption of ≈60% of predicted in asymptomatic patients. [64][65][66][67][68][69][70] A lower maximal oxygen consumption has been associated with worse outcomes in patients with a Fontan procedure. 69,70 A maximal oxygen consumption <50% of the expected for the congenital heart lesion has been proposed as an indication for listing.…”
Section: Indications For Transplantation In Chd 93mentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise performance after palliation of complex congenital heart lesions such as the atrial switch procedure or the Fontan procedure is impaired, with a maximal oxygen consumption of ≈60% of predicted in asymptomatic patients. [64][65][66][67][68][69][70] A lower maximal oxygen consumption has been associated with worse outcomes in patients with a Fontan procedure. 69,70 A maximal oxygen consumption <50% of the expected for the congenital heart lesion has been proposed as an indication for listing.…”
Section: Indications For Transplantation In Chd 93mentioning
confidence: 99%
“…[64][65][66][67][68][69][70] A lower maximal oxygen consumption has been associated with worse outcomes in patients with a Fontan procedure. 69,70 A maximal oxygen consumption <50% of the expected for the congenital heart lesion has been proposed as an indication for listing. 11 In some circumstances, this may result in a maximal oxygen consumption value lower than the 15-mL·kg −1 ·min −1 maximal oxygen consumption commonly used as an indication for transplantation in the adult heart failure population.…”
Section: Indications For Transplantation In Chd 93mentioning
confidence: 99%
“…351 Vȯ 2 max has been found to be an independent predictor of death or hospitalization in a variety of congenital heart defects, including tetralogy of Fallot, 352 repair of transposition of the great arteries, 353 and Fontan physiology. 354 Similarly, in a recent study, Fontan patients with a peak HR <123 bpm were found to have a 10.6-fold greater risk of death during a follow-up period of 4.0±2.0 years. 354 In that study, however, almost all of the patients with a low peak HR had undergone treatments for serious rhythm disturbances.…”
mentioning
confidence: 99%
“…5 Reduced peak oxygen consumption is associated with increased mortality. 6 Thromboembolism is common. 7 A low flow venous state with potential for stasis, multiple suture sites, and synthetic materials, as well as a relatively low cardiac output, all increase the risk.…”
Section: Clinical Consequences Of the Fontan Circulationmentioning
confidence: 99%